Integrasi Nilai-Nilai Pendidikan Karakter pada Mata Pelajaran Matematika dengan Modif COC KOBE - Ediyanto, Arif (SCAD Independent, 2023)
The implementation of character values ​​integration in the classroom is carried out by: (1) exploring student potential/exploring student talents and potential, (2) conducting a learning contract (KOBE) or joint agreement on learning habits in schools, (3) designing meaningful learning, and (4) giving awards. As for outside learning, it is carried out by: (1) creating a guidebook for developing character/character for teachers and staff, (2) creating a book of achievement targets for students, and (3) conducting socialization and cooperation with the school community. The results of the integration of character values ​​in learning are: (1) teachers handle students more optimally because based on the results of learning modality tests and talent and interest tests, they will know how students' learning styles, types of intelligence they have, their learning tendencies, and their talents/interests they have, (2) the growth of positive student character, (3) students can gain meaningful learning experiences and teachers are able to actualize competencies by designing child-friendly learning and utilizing ICT.